Estudio de factibilidad para la creación de una empresa productora y exportadora de pasta de cacao, cantón Buena Fe, año 2015 - Suárez Tubay, Luis Alberto (2015)
The present INVESTIGATION PROJECT, was made in the Buena fe Corner period 2015, where it was examined as primary target "FEASIBILITY STUDY FOR the CREATION OF a PRODUCING and EXPORTING COMPANY OF PASTE OF CACAO IN the BUENA FE CORNER YEAR 2015 ". Although Ecuador is one of the most important countries in the commerce of grain cacao, this escaza has one supply of half-finished due to the investment as far as the machinery that is due to do for the elaboration of this product. The company will be located in the Buena fe Corner province Los Rios since this account with a better access to the small and medium cacao paste producers which will allow an uninterrupted supply of the raw material as they are the grains of dry cacao semi. The control of quality of the cacao paste will be based on the technical requirements of the INEN that is in charge to regularize the microbiological and component requirements of cacao paste. The company it raises to monthly produce 10.37 tons of cacao paste, which is equivalent to a total of 124.44 tons annual. For which an investment of $254,872.13 for the construction of Planta the Production will be made, purchase of Machinery, Equipment of Production, Equipment of Computation and mainly for the capital of work for the first 3 months of production. Amount that will be financed by the contribution of 4 partners and a loan that will be made to the National Bank of Promotion with an interest of annual 10% to ten years term.